Placental expression of sFlt-1 and PlGF in early preeclampsia vs. early IUGR vs. age-matched healthy pregnancies - Alice Hoeller; Laura Ehrlich; Michaela Golic; Florian Herse; Frank H. Perschel; Monika Siwetz; Wolfgang Henrich; Ralf Dechend; Berthold Huppertz; Stefan Verlohren (Taylor & Francis Group, 2017)
Objective: To investigate whether differences between early preeclampsia and early fetal growth restriction can be explained by differential placental expression patterns of sFlt-1, Flt-1, and PlGF. Methods: Placental tissues and maternal blood samples from six cases of preeclampsia, seven IUGR, and six age-matched controls were studied for mRNA and protein levels as well as protein localization and expression intensity. Results: Neither placental PlGF mRNA and protein expression nor placental villous trophoblast expression intensity of PlGF was altered by placental dysfunction. Conclusion: High sFlt-1 concentrations may account for diminished maternal serum PlGF levels.